Christmas is not just for Christmas: an exploration of the Christmas story and its meaning, as told by members of the congregation at the Festival of Nine Lessons and Carols held at York Minster on Christmas Eve 2007 - Phillips, Rachel (2011)
This thesis explores the content and meaning of the Christmas Story, as expressed by members of the congregation at York Minster on Christmas Eve 2007. The work was developed through a Pilot Study in York Minster and Derby Cathedral over Christmas 2006, involving telephone and email interviews and Focus Group discussions. This enabled a questionnaire to be developed for use at York Minster’s Festival of Nine Lessons and Carols, held on Christmas Eve 2007; the questionnaires invited Respondents to tell the Christmas Story in their own words and to say what they thought the Christmas Story means. Completed questionnaires were analysed using grounded theory, and themes of the Respondents’ understanding emerged. These themes are explored in relation to passages of Scripture read in the service and to carols sung in the service. The explicit and implicit theology of the Respondents is then compared with orthodox Christian belief, as set out in the Nicene Creed, in order to explore how Respondents’ understanding did or did not correlate with what the Church of England believes. There is then reflection on issues which those constructing Christmas carol services might usefully take in to account. The thesis concludes by proposing theories for testing in further research.